Dual AAV/IL-10 Plus STAT3 Anti-Inflammatory Gene Delivery Lowers Atherosclerosis in LDLR KO Mice, but without Increased Benefit - Maohua Cao; Junaid A. Khan; Bum-Yong Kang; Jawahar L. Mehta; Paul L. Hermonat (International Journal of Vascular Medicine)
Both IL-10 and STAT3 are in the same signal transduction pathway, with IL-10-bound IL10 receptor (R) acting through STAT3 for anti-inflammatory effect. To investigate possible therapeutic synergism, we delivered both full-length wild-type human (h) STAT3 and hIL-10 genes by separate adenoassociated virus type 8 (AAV8) tail vein injection into LDLR KO on HCD. Compared to control Neo gene-treated animals, individual hSTAT3 and hIL-10 delivery resulted in significant reduction in atherogenesis, as determined by larger aortic lumen size, thinner aortic wall thickness, and lower blood velocity (all statistically significant). However, dual hSTAT3/hIL-10 delivery offered no improvement in therapeutic effect. Plasma cholesterol levels in dual hSTAT3/hIL-10-treated animals were statistically higher compared to hIL-10 alone. While no advantage was seen in this case, we consider that the dual gene approach has intrinsic merit, but properly chosen partnered genes must be used.